Improving farmers' participation in the warehouse receipt system - Azizah Nazzala Fauzi (Center for Indonesian Policy Studies (CIPS), 2023)
The warehouse receipt system (WRS) (Sistem Resi Gudang or SRG) is a system that allows farmers to store their harvest at a receipt-issuing warehouse, receive a receipt as a proof of ownership for the commodities stored, and release the harvest to the market for a higher price. The WRS system is intended as a tool to help increase access to financing for farmers, farmer groups, and cooperatives. Receipts for stored harvests can be presented as collateral to banks or other financial institutions. In this way, the WRS allows farmers to delay sales to obtain a better price while providing access to financing through the receipt. Despite offering farmers access to financing and an increase in income, sixteen years after its establishment in Indonesia, WRS is still not used widely by farmers. According to Statistics Indonesia's data from 2017, in Cianjur and Subang, West Java Province there were only 800 rice farmers that used WRS out of 324,558 farmers (Gunawan, 2019). WRS in Indonesia is regulated under Law No. 9/2006 on Warehouse Receipt System, which was amended by Law No. 9/2011. The governing legislation outlines the division of tasks in the implementation and operation of WRS. The Commodity Futures Trading Regulatory Agency (Badan Pengawas Perdagangan Berjangka Komoditi or Bappebti) is mandated under the Ministry of Trade (MOT) to regulate, supervise, and develop WRS implementation and activities.
Keywords: 330